Effects of resilience, social support, and academic self-efficacy, on mental health among Peruvian university students during the pandemic: the mediating role of digital inclusion - Cassaretto, Mónica; Espinosa, Agustín; Chau, Cecilia (Frontiers in Psychology, 2024)
Background Mental health of university students has been impacted during the pandemic, highlighting the importance of understanding its psychosocial determinants. Nevertheless, there has been limited exploration into whether the digital inclusion conditions for remote education could mediate the effects that variables such as resilience, social support, and academic self-efficacy may have on mental health. Considering the above, there is evidence that shows a consistent relationship between resilience, social support and academic self-efficacy on mental health, to the extent that these are psychological variables. On the other hand, digital inclusion, which comprehends a contextual variable, not a psychological one, related to ICT access opportunities and mainly focused on the quality of Internet access, should be analyzed in a differential manner. Objectives This study seeks to analyze the effect of resilience, social support and academic self-efficacy, on the mental health of a group of Peruvian university students; in addition, it seeks to analyze the mediating role of digital inclusion. Materials and methods A cross-sectional study was conducted with 3,147 undergraduate students from a private university in Lima, Perú. From August to October 2020, data were collected online through questionnaire, this include The Depression, Anxiety and Stress Scale 21 (DASS-21), The 10-item version of the Connor-Davidson Resilience Scale (CD-RISC10), The Multidimensional Scale of Perceived Social Support (EMASP), The Perceived Self-Efficacy Specific for Academic Situations Scale (EAPESA) and to measure digital inclusion, the Perceived Quality of Internet Access reported by the students. The levels of participants’ anxiety, depression and stress were described using frequency and percentage. Pearson Correlation test was used to measure the correlation between the variables and a Path analysis was conducted. Finally, The PROCESS macro for SPSS (Model 4) was applied to examine the mediating effect of the model controlling gender variable. Results The results revealed significant levels of extremely severe symptoms of anxiety (36.8%), depression (33.4%) and stress (18.1%) among the participants. A path analysis, which indicated that resilience (β = −0.346), social support (β = −0.189), academic self-efficacy (β = −0.060) and digital inclusion (β = −0.089) had significant impact on students’ General Distress. In addition, digital inclusion plays a partial mediation role with low but significant effect size in the relationship between resilience, social support and self-efficacy with mental health. Conclusion Mental health of university students during the pandemic shows alarming levels of general or emotional distress. The findings indicate that resilience, social support and self-efficacy protect college students’ mental health by reducing general distress. However, the study shows that when there is a digital divide around internet quality the impact of these factors is affected.